Can a Higher Protein/Low Glycemic Index vs. a Conventional Diet Attenuate Changes in Appetite and Gut Hormones Following Weight Loss? A 3-Year PREVIEW Sub-study - Buso, Marion E.C.; Seimon, Radhika V.; McClintock, Sally; Muirhead, Roslyn; Atkinson, Fiona S.; Brodie, Shannon; Dodds, Jarron; Zibellini, Jessica; Das, Arpita; Wild-Taylor, Anthony L.; Burk, Jessica; Fogelholm, Mikael; et al. (Frontiers in Nutrition, 2021)
Background: Previous research showed that weight-reducing diets increase appetite sensations and/or circulating ghrelin concentration for up to 36 months, with transient or enduring perturbations in circulating concentrations of the satiety hormone peptide YY. Objective: This study assessed whether a diet that is higher in protein and low in glycemic index (GI) may attenuate these changes. Methods: 136 adults with pre-diabetes and a body mass index of ≥ 25 kg/m2 underwent a 2-month weight-reducing total meal replacement diet. Participants who lost ≥ 8% body weight were randomized to one of two 34-month weight maintenance diets: a higher protein and moderate carbohydrate (CHO) diet with low GI, or a moderate protein and higher CHO diet with moderate GI. Both arms involved recommendations to increase physical activity. Fasting plasma concentrations of total ghrelin and total peptide YY, and appetite sensations, were measured at 0 months (pre-weight loss), at 2 months (immediately post-weight loss), and at 6, 12, 24 and 36 months. Results: There was a decrease in plasma peptide YY concentrations and an increase in ghrelin after the 2-month weight-reducing diet, and these values approached pre-weight loss values by 6 and 24 months, respectively (P=.32 and P=.08, respectively, versus 0 months). However, there were no differences between the two weight-maintenance diets. Subjective appetite sensations were not affected by the weight-reducing diet nor the weight-maintenance diets. While participants regained an average of ~50% of the weight they had lost by 36 months, the changes in ghrelin and peptide YY during the weight-reducing phase did not correlate with weight regain. Conclusion: A higher protein, low GI diet for weight-maintenance does not attenuate changes in ghrelin or peptide YY compared with a moderate-protein, moderate GI diet. Clinical trial registry: ClinicalTrials.gov registry ID NCT01777893 (PREVIEW) and ID NCT02030249 (Sub-study)